Analysis of Sirah Learning Model at MATSA, Malaysia and Dayah Darul Muta'allimin, Aceh: Between Traditional and Contemporary Educational Institutions - Muhammad Aulia; Khairuddin Hasan; Muhammad Iqbal; Mohd Lokman Bin Marzuki (Al-Tarbawi Al-Haditsah: Jurnal Pendidikan Islam, 2025)
The research aims to determine the depth of sirah material in MATSA, Malaysia, and Dayah Darul Muta'allimin, Aceh, collecting data related to the teaching sources used, methods used, media variations, and evaluation of learning implemented. The research uses a multi-site qualitative approach, with data collection techniques such as interviews, observations, and document studies. Data were collected using validated instruments. Data analysis involves data reduction, data presentation, and conclusion. The research results show that the scope of Sirah's learning material taught at the intermediate level is generally relatively similar. The teaching resource at MATSA, Malaysia, uses the book "Kitab al Sirah al Nabawiyyah" by Yayasan Islam Kelantan. At Dayah Darul Muta'allimin, the "Kitab Khulashah Nurul Yaqin" by Syekh Umar Abdul Jabbar is used. Even so, the difference in the teaching resources used makes the learning of sirah in Dayah Darul Muta'allimin more traditional. The methods used are Arabic text translation techniques and storytelling techniques. The media used are Microsoft PowerPoint and the Kahoot application. The research contributes to the development of learning models in Islamic education. The learning model applied to modern Islamic educational institutions in Malaysia can be combined with Aceh's traditional educational learning model.Keywords: Sirah Learning, MATSA Malaysia, Dayah Darul Muta’allimin Aceh.